Analisis UX pada Aplikasi Komik Digital Menggunakan Metode Usability Testing - Nanda Asmara Ramdhan Putra; I Gede Arta Wibawa (Jurnal Nasional Teknologi Informasi dan Aplikasinya, 2025)
The shift to digital media has intensified competition among comic applications, making User Experience (UX) a critical determinant of success. This study evaluates a digital comic app's UX via Usability Testing with five users , measuring effectiveness, errors, learnability, and satisfaction.Results indicate a 100% task completion rate , yet a high error rate of 60% reveals significant usability issues. The "Change Notification" and "Download Offline" features were the primary sources of errors , scoring lowest in learnability. Interestingly, high user satisfaction contrasts with the high error rate , suggesting users encountered non-critical errors that hindered efficiency but did not spoil the overall experience. In conclusion, while functionally effective , the application requires a targeted redesign of its notification and download features to improve usability.